El joven Karl Marx : filosofía alemana, política moderna y realización humana - Leopold, David (Akal universitaria, 2012)
This text presents a study of Karl Marx's early writings. They provide the fascinating spectacle of a powerful and imaginative intellect wrestling with complex and significant issues, but they also present formidable interpretative obstacles to modern readers.